Estimated direct costs of non-small-cell lung cancer by stage and care phase: a whole disease model. (30th September 2020) - De Luca, G; Buja, A; Rivera, M; De Polo, A; Marchetti, M; Scioni, M; Pasello, G; Bortolami, A; Schiavon, M; Conte, P F
Abstract: Background: Non-small-cell lung cancer (NSCLC) is the first cause of cancer-related death among men and the second among women worldwide. It also poses an economic threat to the sustainability of healthcare services. This study estimates the direct costs of care for patients with NSCLC by stage at diagnosis and management phase of pathway recommended in local and international guidelines. Methods: Based on the most up-to-date guidelines we developed a detailed "whole-disease" model that lists the probabilities of all potentially necessary diagnostic and therapeutic actions involved in the management of each stage of NSCLC. Then we assigned the cost sustained by the public authorities to each procedure, obtaining an estimate of the total and average per-patient costs of each stage of the disease and management phase in Veneto Region, Italy. Results: The mean expected cost of a patient with NSCLC is 22, 968 € in the first year: 20, 222 € in stage I, 23, 935 € in stage II, 23, 027 € in stage III, 22, 915 € in stage IV and 31, 749 € for Pancoast's tumors. In the second year the mean per patient-costs patient ranged from 2, 722 €, for a patient with stage I disease, to 13, 396 € for a patient with stage IV, with an overall average cost of 8, 307 €. In the early stages, the main cost was due to surgery, whereas in the more advanced stages radiotherapy, medical therapy, treatment for progressions and supportive care become variously more important. Conclusions: Our study enabled a prediction of the direct costs and outcomes for patients diagnosed with NSCLC on a two-year timeline after the diagnosis. An estimation of the direct costs of NSCLC, and in general for cancer, appears fundamental to predict the burden of new oncological therapies and treatments on healthcare services, and, in our opinion, our model could represent a useful tool for policy-makers in the optimization of resources allocation. Key messages: Whole disease model allows an economic evaluation of a clinical pathway. The model is able to estimate direct costs of NSCLC by disease stage and management phase within a time horizon of two years. High cost-surgery makes the early stages no less expensive than advanced stages during the first year. In the second year, an advanced stage case costs almost five times more than an early stage case.